2021
DOI: 10.2147/opth.s313158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dry Eye Disease on Work Productivity Among Saudi Workers in Saudi Arabia

Abstract: Purpose To assess the impact of dry eye disease (DED) on work productivity in Saudi Arabia and investigate its effect on daily activities. Patients and Methods We conducted a cross-sectional study on male and female Saudi workers age 20 years or older. The data were collected via self-administered questionnaires distributed electronically through social media. We used the Ocular Surface Disease Index questionnaire to diagnose DED patients and assess their DED severity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this cross-sectional study, the calculated study sample using the OpenEpi web tool, with a 95% confidence level and an estimated prevalence of 32.1%, was 337 participants [2]. We used the validated Arabic version of the OSDI [7] to diagnose DED. The OSDI is a 12-item questionnaire that assesses the severity of dry eye according to a score that ranges between 0 and 100.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this cross-sectional study, the calculated study sample using the OpenEpi web tool, with a 95% confidence level and an estimated prevalence of 32.1%, was 337 participants [2]. We used the validated Arabic version of the OSDI [7] to diagnose DED. The OSDI is a 12-item questionnaire that assesses the severity of dry eye according to a score that ranges between 0 and 100.…”
Section: Methodsmentioning
confidence: 99%
“…We used the validated Arabic version of the OSDI [ 7 ] to diagnose DED. The OSDI is a 12-item questionnaire that assesses the severity of dry eye according to a score that ranges between 0 and 100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One Saudi Arabian study found that the decrease in work productivity was higher among people who were suffering from severe symptoms. The results also showed that these people not only decreased their performance at work but also at home, which affected their overall quality of life [ 32 ]. In our study, the most commonly reported activities that participants struggled with reading street signs or the names of stores, reading ordinary print in newspapers, and finding something on a crowded shelf.…”
Section: Discussionmentioning
confidence: 99%